2003
DOI: 10.1063/1.1556257
|View full text |Cite
|
Sign up to set email alerts
|

Highly oriented nonepitaxially grown L1 FePt films

Abstract: A method of preparing nonepitaxially grown, highly textured L1 0 FePt thin films is described. A nearly perfect ͑001͒ texture was obtained by direct deposition of FePt films on Corning 7059 glass substrates and subsequent rapid thermal annealing. The ordering and orientation of the L1 0 -phase FePt grains were controlled by the initial as-deposited film structure, and also by the annealing process. Magnetic measurements reveal large perpendicular anisotropy for these ͑001͒ textured films. The substrates and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(61 citation statements)
references
References 7 publications
2
56
0
3
Order By: Relevance
“…4 -6 The fabrication conditions, annealing processes, and magnetic properties of these ͑001͒ textured films also have been investigated systematically. [5][6][7][8][9] For practical applications, nonepitaxially grown L1 0 nanocomposite FePtbased thin films are advantageous because of the ease of growth. In this letter, we report the design and fabrication of nonepitaxially grown ͑001͒ textured L1 0 nanocomposite FePt:C thin films with a soft-magnetic underlayer ͑SUL͒.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 -6 The fabrication conditions, annealing processes, and magnetic properties of these ͑001͒ textured films also have been investigated systematically. [5][6][7][8][9] For practical applications, nonepitaxially grown L1 0 nanocomposite FePtbased thin films are advantageous because of the ease of growth. In this letter, we report the design and fabrication of nonepitaxially grown ͑001͒ textured L1 0 nanocomposite FePt:C thin films with a soft-magnetic underlayer ͑SUL͒.…”
mentioning
confidence: 99%
“…The details regarding the attainment of these preferential ͑001͒ oriented FePt-based composite films and their perpendicular magnetic properties have been reported and discussed in our previous papers. 5,7 In order to study exchange coupling between magnetic grains, the correlation length of this sample was analyzed by MFM. Figure 3 shows the MFM image for an 11 nm thick FePt:C film in the thermally demagnetized states.…”
mentioning
confidence: 99%
“…The most common methods to obtain the c-axis normal to the fi lm plane [(0 0 1) texture] are to use seed or buffer layers, such as MgO. Recently, non-epitaxially grown, highly (0 0 1)-textured L1 0 FePt [9,10] and FePt based fi lms [18] have been obtained by using multilayer deposition plus post annealing. It is found that orientations of FePt grains are affected by many preparation parameters, such as initial as-deposited fi lm structure, composition, annealing time and so on [19,20].…”
Section: Fept(cf X ) Core-shell Nanoclusters With C Matrixmentioning
confidence: 99%
“…In this paper, we report on recent efforts to fabricate high-anisotropy L1 0 FePt nanocomposite fi lms by three methods: monodispersed core-shell FePt(CF x ) nanocluster-assembled fi lms grown with a gas-aggregation source [8,9], (0 0 1)-oriented FePt L1 0 nanocomposite fi lms synthesized by non-epitaxial growth of multilayers [10,11], chemical synthesis of FePt L1 0 particles in nanoporous alumina and creation of highly anisotropic particle fi lms under external magnetic fi eld [12], and analytical and numerical simulational results on these systems [13].…”
Section: Introductionmentioning
confidence: 99%
“…The multilayering of Fe/ Pt and dimensions of the Fe and Pt individual layers, annealing temperature and time, total film thickness, alloy composition, etc., appear to play an important role in obtaining the films with c axis perpendicular to the film plane. 3,4 Recent modeling results suggested that the media for future 1 Tbit/ in. 2 should have small grain size ͑d ϳ 4 nm͒ and narrow distribution ͑ / d ϳ 0.07͒, moderate anisotropy ͑H k ϳ 25 kOe͒, coercivity ͑H c ϳ 5-8 kOe͒, and saturation magnetization ͑M s ϳ 750 emu/ cc͒.…”
Section: Introductionmentioning
confidence: 99%